Gut microbiota trigger host liver immune responses that affect drug-metabolising enzymes - Rao, Jiaoyu; Qiu, Peng; Zhang, Yonggang; Wang, Xiaokang (Frontiers in Immunology, 2024)
There is increasing evidence that the intestinal microbiota plays an integral role in disease pathogenesis and treatment. Specifically, the intestinal microbiota significantly influences the pharmacokinetics and pharmacodynamics of orally administered drugs through direct involvement in drug metabolism and, consequently, drug bioavailability. However, the gut microbiota also exerts immunoregulatory effects on the liver—the organ primarily responsible for drug metabolism—thereby indirectly impacting the body’s capacity to metabolise and process drugs. Individual differences in this pathway substantially contribute to the variability in clinical drug treatment outcomes observed between patients. This review examines the impact of liver immune responses, as triggered by the intestinal microbiota, on the activity of drug-metabolising enzymes and discusses the implications for precision medicine.